2016
DOI: 10.1177/2158244016656230
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Youngsters’ Gender Role Attitudes and Individual, Home, and School Characteristics

Abstract: Because of the importance of gender role attitudes (GRA) for both academic and social outcomes, it is crucial to understand how GRA is constructed and changes over time. A systematic literature review was conducted to look into the relationship between youngsters' GRA and individual, home, and school characteristics. Thirty-five international studies were identified through searches in different databases. The review reveals that the studies mostly apply a deterministic view to studying the construction of GRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 88 publications
(265 reference statements)
5
26
0
Order By: Relevance
“…not just those concerned with decision making). This extends prior population‐level research where investigation of this differential has been limited to measures of household decision making (Pepin & Cotter, 2018) and conflict between women's roles in the workplace and as mothers (Halimi et al, 2016).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…not just those concerned with decision making). This extends prior population‐level research where investigation of this differential has been limited to measures of household decision making (Pepin & Cotter, 2018) and conflict between women's roles in the workplace and as mothers (Halimi et al, 2016).…”
Section: Discussionsupporting
confidence: 59%
“…Although there are numerous scales to measure GI (Davis & Greenstein, 2009; Halimi et al, 2016), in this section, we focus on findings from population‐level surveys, which, due to their robust sampling procedures, facilitate population inferences. However, population studies have some limitations when compared to smaller studies as they generally require measurement parsimony (to contain interview length) and continuity in item wording over survey waves (if measuring change over time) (Walter, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, the results of this work add more evidence to the abundant literature establishing that men are significantly more traditional (Blázquez-Alonso et al, 2019;Bugay et al, 2019;Halimi et al, 2016). In this context, it is striking that the first and third most difficult ideas to modify are the only which refer exclusively to stereotypes of male.…”
Section: Discussionsupporting
confidence: 65%
“…Recent studies relate this traditional mentality with, for example, dating violence (Bringas-Molleda et al, 2017;Carrascosa et al, 2019;García-Cueto et al, 2015;Gracia-Leiva et al, 2019: Martínez-Gómez et al, 2021Pérez et al, 2020), intimate partner violence attitude (Evcili & Daglar, 2021), sexual double standard (Kim et al, 2019;Martínez-Gómez et al, 2021), or the agreement with conservative policies and the hierarchy and inequality in society (Bugay et al, 2019). Furthermore, in both western and non-western societies, men have a more traditional mentality than women (Blázquez-Alonso et al, 2019;Bugay et al, 2019;Halimi et al, 2016). Cotter, Hermsen, and Vaneman (2011) argue that we live in an emergent cultural frame called egalitarian essentialism.…”
Section: Introductionmentioning
confidence: 99%
“…Social influences included education, work, and digital media access. Several studies have observed the effect of education on gender role attitudes [ 36 , 37 ], although some have noted that increased schooling does not always enhance gender egalitarian views [ 38 , 39 ]. In our study, educational attainment led to significantly more equitable gender attitudes among older girls and older boys, however, effect sizes were relatively small.…”
Section: Discussionmentioning
confidence: 99%